2016
DOI: 10.1002/2015gl066446
|View full text |Cite
|
Sign up to set email alerts
|

Terrane‐controlled crustal shear wave splitting in Taiwan

Abstract: Taiwan is the result of arc‐continent collision associated with the convergence of the Philippine Sea plate with the eastern Eurasian plate continental margin. The locus of deformation is found in eastern Taiwan in the form of mountain building (Central Range) with underlying thickened lithosphere. Rapid tectonic exhumation in the Central Range has uncovered low‐to‐high‐grade metamorphic rocks marked by steep cleavage. We carried out a crustal seismic anisotropy study across Taiwan, producing a database of ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…This suggests that fast directions can be controlled by local‐scale geological blocks. A similar observation was reported by Okaya et al () showing that patterns of fast directions correlate with tectonic terranes across the Southern Central Range in Taiwan. They inferred that minerals in metamorphic rocks might form preferred alignment due to crustal deformation.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that fast directions can be controlled by local‐scale geological blocks. A similar observation was reported by Okaya et al () showing that patterns of fast directions correlate with tectonic terranes across the Southern Central Range in Taiwan. They inferred that minerals in metamorphic rocks might form preferred alignment due to crustal deformation.…”
Section: Discussionsupporting
confidence: 89%
“…Figure shows that the theoretically predicted ϕ is orogen‐parallel at about 20° with δ t roughly 0.2 s for most Ω. This agrees with the general results of Okaya et al () who measured local shear wave splitting to obtain δ t of 0.1–0.5 s and ϕ more or less orogen‐parallel along the mountain range (the Hsuehshan Range and the Central Range). Kuo et al () using local intraslab events observed δ t < 0.1 s in northern Taiwan, also suggesting little net anisotropy along the path traveling through the lithosphere.…”
Section: Discussionsupporting
confidence: 89%
“…Near the surface, cracks and active faults aligned by tectonic stress are major detectable fabrics (e.g., Chang et al, ; Chen et al, ). A few kilometers into the upper crust, cracks closed and subvertical foliation/cleavage planes and terrain boundary faults developed during the arc‐continent collision dominate, producing orogen‐parallel anisotropy (Huang et al, ; Okaya et al, ). The lower crust, or the crust of the underthrusted EP lithosphere, likely undergoes subduction‐induced shear that yields convergence‐parallel anisotropy (Huang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…; Okaya et al . ). We want to draw special attention on receiver function studies, which have observed the pattern of the converted Ps waves for several anisotropic scenarios (e.g.…”
Section: Anisotropymentioning
confidence: 97%
“…Effects of seismic anisotropy within the crust have been often observed in body and surface waves (e.g. Ozacar and Zandt 2004;Sherrington, Zandt and Frederiksen 2004;Bostock and Christensen 2012;Bianchi et al 2016;Okaya et al 2016). We want to draw special attention on receiver function studies, which have observed the pattern of the converted Ps waves for several anisotropic scenarios (e.g.…”
Section: A N I S O T R O P Ymentioning
confidence: 99%